Sonographic Pearls for Imaging the Brachial Plexus and Its Pathologies - Hsu, Po-Cheng; Chang, Ke-Vin; Mezian, Kamal; Naňka, Ondřej; Wu, Wei-Ting; Yang, Yi-Chiang; Meng, Stefan; Ricci, Vincenzo; Özçakar, Levent (Diagnostics, 2020)
The brachial plexus (BP) is a complicated neural network, which may be affected by trauma, irradiation, neoplasm, infection, and autoimmune inflammatory diseases. Magnetic Resonance Imaging is the preferred diagnostic modality; however, it has the limitations of high cost and lack of portability. High-resolution ultrasound has recently emerged as an unparalleled diagnostic tool for diagnosing postganglionic lesions of the BP. Existing literature describes the technical skills needed for prompt ultrasound imaging and guided injections for the BP. However, it remains particularly challenging for beginners to navigate easily while scanning its different parts. To address this, we share several "clinical pearls" for the sonographic examination of the BP as well as its common pathologies.